Oral squamous cell carcinoma grading classification using deep transformer encoder assisted dilated convolution with global attention - Ramya, Singaraju; Minu, R. I. (Frontiers in Artificial Intelligence, 2025)
In recent years, Oral Squamous Cell Carcinoma (OSCC) has been a common tumor in the orofacial region, affecting areas such as the teeth, jaw, and temporomandibular joint. OSCC is classified into three grades: “well-differentiated, moderately differentiated, and poorly differentiated,” with a high morbidity and mortality rate among patients. Several existing methods, such as AlexNet, CNN, U-Net, and V-Net, have been used for OSCC classification. However, these methods face limitations, including low ACC, poor comparability, insufficient data collection, and prolonged training times. To address these limitations, we introduce a novel Deep Transformer Encoder-Assisted Dilated Convolution with Global Attention (DeTr-DiGAtt) model for OSCC classification. To enhance the dataset and mitigate over-fitting, a GAN model is employed for data augmentation. Additionally, an Adaptive Bilateral Filter (Ad-BF) is used to improve image quality and remove undesirable noise. For accurate identification of the affected region, an Improved Multi-Encoder Residual Squeeze U-Net (Imp-MuRs-Unet) model is utilized for segmentation. The DeTr-DiGAtt model is then applied to classify different OSCC grading levels. Furthermore, an Adaptive Grey Lag Goose Optimization Algorithm (Ad-GreLop) is used for hyperparameter tuning. The proposed method achieves an accuracy (ACC) of 98.59%, a Dice score of 97.97%, and an Intersection over Union (IoU) of 98.08%.